A ‘preterit’ Agenda Magna for 2013 - Verdoy, Alfredo (Razón y fe, 2018)
An agenda has to do with «what needs to be done in the future» and preterit (or simple past tense) with ‘what took place or happened in the past’. It is impossible to do now what has already taken place in the past; therefore, it is not possible to have a preterit agenda. However, the title of his editorial is not a literary oxymoron, but rather a technical descriptor of reality: in 2013 there will be a need to pose and resolve the new problems that arise his year but also but to look at the most important ones that were posed, or were badly posed, or were not resolved, or were badly resolved in the past. What we propose is an agenda that comes from the people, from civil society, and not from any kind of power or authority. We have grouped, under three sections, the urgent requests that we as citizens would like to pose to the State. They involve its there joint powers: legislative, executive and judicial. All tree must, independently, recover lost time and move towards reaching stable solutions for the governance of Spain. However, in this editorial we direct these requests to the Executive power, since if it does not fulfil its legislative functions, as well as its duties of enforcing the compliance of laws and of carrying out sentences handed out by judges, any agenda of three powers. Including the Executive, will be pointless.
Keywords: agenda; problems; civil society; solutions